2016
DOI: 10.1556/2006.5.2016.042
|View full text |Cite
|
Sign up to set email alerts
|

Internet Gaming Disorder Among Slovenian Primary Schoolchildren: Findings From a Nationally Representative Sample of Adolescents

Abstract: Background and aimsSince the inclusion of Internet Gaming Disorder (IGD) in the latest (fifth) edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) as a tentative disorder, a few psychometric screening instruments have been developed to assess IGD, including the 9-item Internet Gaming Disorder Scale – Short-Form (IGDS9-SF) – a short, valid, and reliable instrument.MethodsDue to the lack of research on IGD in Slovenia, this study aimed to examine the psychometric properties of the IGDS9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
88
5
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 179 publications
(112 citation statements)
references
References 44 publications
13
88
5
6
Order By: Relevance
“…The IGDS9-SF was developed to be utilized in large-scale surveys. The validity of both versions has been confirmed in the Spanish-, Portuguese-, and Slovenian-speaking samples (Fuster, Carbonell, Pontes, & Griffiths, 2016; Pontes & Griffiths, 2016; Pontes, Macur, & Griffiths, 2016). …”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The IGDS9-SF was developed to be utilized in large-scale surveys. The validity of both versions has been confirmed in the Spanish-, Portuguese-, and Slovenian-speaking samples (Fuster, Carbonell, Pontes, & Griffiths, 2016; Pontes & Griffiths, 2016; Pontes, Macur, & Griffiths, 2016). …”
Section: Introductionmentioning
confidence: 76%
“…All factor loadings were statistically significant and relatively high, demonstrating that all items were good construct indicators. These results generally corroborated prior validity studies (Fuster et al., 2016; Pontes & Griffiths, 2015, 2016; Pontes et al., 2016). However, the unexpected covariance between the residual errors for Items 6 and 7 was theoretically justifiable as the two items might be referred to the same criterion (i.e., conflict).…”
Section: Discussionmentioning
confidence: 99%
“…Among the short instruments used to assess PGB suggested by APA () in the latest edition of DSM, IGDS9‐SF (Pontes & Griffiths, ), is one of the most‐used psychometric scales internationally, providing support concerning its psychometric indicators (i.e., construct, criterion‐related, and concurrent validity) (i.e., Monacis, De Palo, Griffiths & Sinatra, ; Pontes & Griffiths, , ; Pontes, Macur & Griffiths, , Pontes, Macur & Griffiths, ; Wu, Lin, Årestedt, Griffiths, Broström & Pakpour, ). Moreover, the measurement invariance of the IGDS9‐SF (i.e., the factorial structure) has been established cross‐culturally (i.e., across Australia, USA, UK, Albania, and Italy), supporting the configural invariance and in part, the metric and scalar invariance (Palo, Monacis, Sinatra et al ., ; Stavropoulos, Beard, Griffiths, Buleigh, Gomez & Pontes, ).…”
Section: Introductionmentioning
confidence: 99%
“…According to recent studies, the prevalence of PGB among European gamers is between 1.2% and 5.5% based on the DSM‐5 criteria (e.g., Király et al ., , ; Lemmens et al ., ; Pontes, Macur & Griffiths, ; Rehbein, Kliem, Baier, Mößle & Petry, ). A Finnish study found that the risk of PGB among adolescents is 0.9% (Männikkö, Demetrovics, Ruotsalainen, Myllymäki, Miettunen & Kääriäinen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Surveys using nationally representative samples have reported rates of problematic gaming as 8.5% in American youth aged 8-18 years (Gentile, 2009), 1.2% in German adolescents aged 13-18 years (Rehbein, Kliem, Baier, Mößle, & Petry, 2015), 5.5% in Dutch adolescents aged 13-20 years, and 5.4% in Dutch adults (Lemmens, Valkenburg, & Gentile, 2015), 4.3% in Hungarian adolescents aged 15-16 years (Király, Nagygyörgy, Griffiths, & Demetrovics, 2014;Király et al, 2014), 1.4% in Norwegian gamers (Wittek et al, 2016), 1.6% in youth from seven European countries aged 14-17 years (Müller et al, 2015), and 2.5% in Slovenian adolescents aged 12-16 years (Pontes, Macur, & Griffiths, 2016).…”
Section: Online Gaming Addiction: a Brief Overviewmentioning
confidence: 99%